Circulating Biomarkers and Abdominal Aortic Aneurysm Incidence. Issue 7 (18th August 2015) - Folsom, Aaron R.; Yao, Lu; Alonso, Alvaro; Lutsey, Pamela L.; Missov, Emil; Lederle, Frank A.; Ballantyne, Christie M.; Tang, Weihong
<x xml:space="preserve">Abstract</x> Background— The pathogenesis of abdominal aortic aneurysm (AAA) is complex. Cross-sectional studies have connected circulating biomarkers with AAA, but prospective evidence is limited. Methods and Results— In the Atherosclerosis Risk in Communities Study cohort, we measured multiple blood biomarkers of inflammation, hemostasis, thrombin generation, cardiac dysfunction, and vascular stiffness and identified incident AAAs during follow-up using hospital discharge codes. Six biomarkers (white blood cell count, fibrinogen, D-dimer, troponin T, N-terminal pro-brain natriuretic peptide, and high-sensitivity C-reactive protein) were strongly associated positively with AAA incidence. Compared with having none of these 6 biomarkers in the highest quartile, the hazard ratios of AAA for those with 1, 2, 3, or 4 to 6 biomarkers in the highest quartile were 2.2, 3.3, 4.0, and 9.9, respectively (P for trend < 0.0001) after adjustment for other risk factors. Conclusions— This prospective study found that higher concentrations of 6 biomarkers were associated with increased risk of AAA. The more markers that fell into the highest quartile, the higher the AAA risk was. Multiple positive biomarkers identify a subgroup of patients at high risk of AAA.